Technical performance of milk producers in the state of Goiás , Brazil, in the short and long terms - Sousa,Lucas Oliveira de (2012)
The objective of this study was to identify groups of technologically homogeneous milk producers in the State of Goiás and calculate the gains for inefficient producers, considering the ones of better performance (benchmarks) with the same technological level, i.e., in the short term, and the benchmarks in higher technological level, i.e., in the long term. Multivariate statistical analysis techniques were used for the formation of homogeneous producer groups and multi-stage model of data envelopment analysis (DEA) for the estimation of efficiency scores and identification of benchmarks. The results indicated the formation of four groups of producers and indicate that, on average, the dairy farming in Goiás presents mainly characteristics of traditional, less specialized production. Estimated average efficiency for producers as a whole, or efficiency of long-term, was 0.571. The short-term results vary according to the group analyzed, but were higher than the long-term values, indicating that the factor analysis promoted technological homogeneity between the producers of the same group. Results showed a trend in dairy farming of Goiás towards adequacy of the input/output ratio to the standards of less capitalintensive production systems.